2014
DOI: 10.5296/ijafr.v4i1.5410
|View full text |Cite
|
Sign up to set email alerts
|

IFRS Adoption and Enforcement as Antecedents of Economic Growth

Abstract: This paper assesses the impact of IFRS adoption on the economic growth of adopting countries taking into consideration the level of enforcement of the adopting countries. We hypothesize that the adoption of IFRS increases the economic growth of the adopting countries. This effect is to be moderated by the level of enforcement. That is, we hypothesize a positive interaction between enforcement level and IFRS adoption on the economic growth rate of a country. Using several statistical procedures and models to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…Because worldwide adoption is still in its infancy, few studies have been conducted specifically on IFRS adoption at the country level. Traditional neo-classical economics points to economic growth as the incentive for regulatory harmonization, although Zaidi (2012) argues that current research studies do not provide conclusive evidence on the impact of IFRS adoption on countries' economic growth. My research extends previous research on IFRS adoption by identifying groups of countries that choose different IFRS adoption types.…”
Section: Introductionmentioning
confidence: 84%
“…Because worldwide adoption is still in its infancy, few studies have been conducted specifically on IFRS adoption at the country level. Traditional neo-classical economics points to economic growth as the incentive for regulatory harmonization, although Zaidi (2012) argues that current research studies do not provide conclusive evidence on the impact of IFRS adoption on countries' economic growth. My research extends previous research on IFRS adoption by identifying groups of countries that choose different IFRS adoption types.…”
Section: Introductionmentioning
confidence: 84%
“…Foreign direct investment (FDI) has been recognized as an important contributor towards enhancing a country's economic growth (Gordon et al 2012;Zaidi & Huerta 2014;Nor, Wah & Nor 2015;Lungu et al 2017). As such, most countries, especially developing countries target to increase economic growth by attracting FDI into their economies (Iamsiraroj 2016;Thampanishvong & Kannika 2015;Feeny, Iamsiraroj & McGillivray 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most critical means for private sector development to attract foreign direct investors and to raise the confidence of domestic investors is through achieving sustainable public financial management reforms, as well as promoting a more effective corporate governance, accountability, and transparency. Research by Zaidi and Huerta [2] revealed that there is a positive correlation between the adoption of IFRS and the economic growth of the adopting countries as observed five years into implementation. Coffee [3] further supported the idea that improvement in transparency and accounting standards signified an increase in quality of the financial statements, which in turn strengthens investors' trust.…”
Section: Introductionmentioning
confidence: 99%